Testes observacionais de modelos viscosos no formalismo de Eckart - Barbosa, Carolina Martins de Siqueira (2014)
The aim of the present work is to study how the viscous model in uences the evolution and formation of the structure in the Universe. The analysis is performed using Newtonian and neo-Newtonian approaches to cosmology. It is considered that the viscous uid describes the dark components of the universe, not only dark matter but also in some situations, the dark energy. The study is done by placing in the uid equation of state the term of volumetric viscosity